Jamal's solution is accurate because he correctly started with the equation \(x^2 + 4x - 12 = 0\) after setting it equal to zero. He factored it as \((x + 6)(x - 2) = 0\) and correctly used the zero product property to find the solutions \(x = -6\) and \(x = 2\). In contrast, George incorrectly set up his equation as \((x + 5)(x - 1) = 7\), which does not apply the zero product property correctly, leading to inaccurate solutions \(x = -5\) and \(x = 1\); the correct approach should involve bringing all terms to one side to establish the equation as equal to zero before factoring.
use the table to answer the question.
jamal
step 1 set equation =0 x^2+4x-12=0
step 2 write quadratic equation as the product of two factors (x+6) (x-2)=0
step 3 set each factor equal to 0 x+6=0 and x-2=0
step 4 solve each equation x=-6 and x=2
George
step one begin with the equation x^2+4x-5=7
step two write quadratic equation as the product of two factor (x+5) (x-1) =7
step three. set each factor equal to 0 x+5=0 and x-1=0
step four solve each equation x=-5 and x=1
when trying to solve the quadratic equation x^2+4x-5=7 jamal and george each provided their work in tables. each said they used the zero product property to solve the equation after step 2 explain how you know the correct students solution is accurate and how you know the incorrect students is inaccurate. explain in 2-3 sentences
1 answer